National education plan and teaching condition For an ontology of teaching work - Santos, Vinício de Macedo (Universidade Estadual de Campinas, 2016)
The National Education Plan (PNE) produced after the 1988 Constitution has been important for education. Taking into consideration the dispute of interests, space and resources that occur on the planning and on the decision-making procedures the last two PNE proceed by regulating the goals some of the historical requests of educators and the Brazilian society have. However, according to what has occurred in this field, the goals and strategies adopted, the financial restrictions and even the extinction of taxes recently (in 2015)) demonstrate that there is a stark confrontation between political strength and different projects for public education in the country.. In this text PNE goal 7 whose strategies seem to be those that affect teaching practice, learning and teaching development more establishing practices developed informally at the schools and it has influenced the teaching condition.